Ethical learning through meetings with others - Bergmark, Ulrika (The International Journal of Learning: Annual Review, 2007)
Different kinds of meetings are natural for every student and teacher in schools around the world. This study deals with matters of ethics as a relation, meetings with Others, narratives, reflection and learning experiences. In a secondary school in northern Sweden eight students and one teacher worked within a course where different guests were invited into the classroom - a homosexual, a refugee and a disabled person. The aim of this article is to elucidate, enable understanding for and discuss students' and a teacher's learning experiences through their meetings with Others. The empirical data was created through close observation, field notes, reflective journals and e-mail communication. Theoretically the study is based on the philosophies of Emanuel Lévinas and Nel Noddings. Validerad; 2007; 20071113 (ulrber)